Evaluation of optimization parameters in microwave reflux extraction of piperine-oleoresin from black pepper (Piper nigrum) - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth (Elsevier, 2018)
Black pepper is a functional plant with nutritional and medicinal benefits. Piperine being the major bioactive compound in black pepper has been applied for the treatment of many free radical-related diseases. This study determined a combination of operating parameters that optimize the microwave extraction of the piperine oil. The effect of irradiation time, microwave power level, feed particle size and feed-solvent ratio on piperine content and absorbed microwave energy were tested using a three-level L9-Taguchi parametric design. The results obtained placed the optimum extraction condition at 90 min of irradiation time, 350 W of microwave power, 0.1 mm of particle size and 1:12 of feed-solvent ratio. Under this optimal condition the optimal piperine oil and absorbed microwave energy of 5.64 w/w and 84.17 J/min were obtained, respectively. The optimal conditions can therefore be employed to design extraction process with higher efficiency and productivity.